Use of Ergogenic Substances amongst Bodybuilding Athletes Around Polokwane Municipality, Limpopo Province, South Africa - Masoga, Sylven; Wisdom Mboweni, Ntsako; Matlala Ramokolo, Khutso (Arab Journal of Nutrition and Exercise (AJNE), 2023)
Background: Although there is a lack of scientific evidence supporting the use of some ergogenic substances, it remains a common practice among bodybuilding athletes. Nevertheless, the use of ergogenics among bodybuilding athletes around Polokwane Municipality (PM) in Limpopo Province remains unknown. Aim: To determine the use of ergogenic substances amongst bodybuilding athletes around Polokwane municipality in Limpopo Province. Methods: A descriptive study with a purposive sampling technique was used to obtain 51 amateur bodybuilding athletes in gyms around PM. Ethical approval and permission were obtained from the MEDUNSA Research and Ethics Committee (MREC) and coaches respectively. Sampled athletes signed written informed consent forms. Data collection was done using self-designed questionnaires covering the demography, training information, and the use of ergogenic agents. Data were loaded onto the SPSS (v.23) and analyzed. Descriptive tests were used to describe ergogenic use through ranges, percentages, means, and standard deviations (±SD). Results: The majority (94.1%) were males, of which 66.7% participated as bodybuilders for ≤2 years. Almost all athletes (86.3%) trained three to four days a week for 1–3 hr (94.1%) on weekdays. Only 37.3% relied on coaches for nutrition information followed by those who used social media (29.4%), teammates (29.3%), and nutrition experts (4.0%). A few athletes (15.7%) used ergogenics, of them, 13.7% used creatine and 2.0% vitamin capsules. Conclusion: Overall, Polokwane bodybuilders were not using ergogenic agents during their bodybuilding sports careers. Keywords: bodybuilding, ergogenic agents, supplements and athletes